Aerosol Impacts on Water Relations of Camphor (Cinnamomum camphora) - Chi, Chia-Ju Ellen; Zinsmeister, Daniel; Lai, I-Ling; Chang, Shih-Chieh; Kuo, Yau-Lun; Burkhardt, Jürgen (Frontiers in Plant Science, 2022)
Major parts of anthropogenic and natural aerosols are hygroscopic and deliquesce at high humidity, particularly when depositing to leaf surfaces close to transpiring stomata. Deliquescence and subsequent salt creep may establish thin, extraordinary pathways into the stomata, which foster stomatal uptake of nutrients and water, but may also cause stomatal liquid water loss by wicking. Such additional water loss is not accompanied by wider stomatal aperture with larger CO2 influx and hypothetically reduces water use efficiency (WUE). Here, the possible direct impacts of aerosols on physical and physiological parameters of camphor (Cinnamomum camphora) were studied i) in a greenhouse experiment using aerosol exclusion and ii) in a field study in Taiwan, comparing trees at two sites with different aerosol regimes. Scanning electron microscopy (SEM) images showed that leaves grown under aerosol exclusion in filtered air (FA) were lacking the amorphous, flat areas that were abundant on leaves grown in ambient air (AA), suggesting salt crusts formed from deliquescent aerosols. Increasing vapor pressure deficit (VPD) resulted in half the Ball-Berry slope and double WUE for AA compared to FA leaves. This apparent contradiction to the wicking hypothesis may be due to the independent, overcompensating effect of stomatal closure in response to VPD, which affects AA more than FA stomata. Compared to leaves in a more polluted region in the Taiwanese Southwest, NaCl aerosols dominated the leaf surface conditions on mature camphor trees in Eastern Taiwan, while the considerably lower contact 20 angles and the 2.5 times higher minimum epidermal conductances might have come from organic surfactants. Interpretations of SEM images from leaf surface microstructures should consider amorphous areas as possible indicators of aerosol deposition and other hygroscopic material. Amount and type of the material determine the resulting impacts on plant water relations, together with the surrounding atmosphere and ecophysiological traits.